Emerging trends in high-solids enzymatic saccharification of lignocellulosic feedstocks for developing an efficient and industrially deployable sugar platform - Baral, Pratibha; Kumar, Vinod; Agrawal, Deepti (Taylor and Francis, 2021)
For the techno-commercial success of any lignocellulosic biorefinery, the cost-effective production of fermentable sugars for the manufacturing of bio-based products is indispensable. High-solids enzymatic saccharification (HSES) is a straightforward approach to develop an industrially deployable sugar platform. Economic incentives such as reduced capital and operational expenditure along with environmental benefits in the form of reduced effluent discharge makes this strategy more lucrative for exploitation. However, HSES suffers from the drawback of non-linear and disproportionate sugar yields with increased substrate loadings. To overcome this bottleneck, researchers tend to perform HSES at high enzyme loadings. Nonetheless, the production costs of cellulases are one of the key contributors that impair the entire process economics. This review highlights the relentless efforts made globally to attain a high-titer of sugars and their fermentation products by performing efficient HSES at low cellulase loadings. In this context, technical innovations such as advancements in new pretreatment strategies, next-generation cellulase cocktails, additives, accessory enzymes, novel reactor concepts and enzyme recycling studies are especially showcased. This review further covers new insights, learnings and prospects in the area of lignocellulosic bioprocessing.
Keywords: Lignocellulosic biomass; cellulases; high-solids enzymatic saccharification; fermentable sugars; bio-based products